Manufacturing Processes and Materials for Engineers - Doyle, Lawrence E. (Prentice-Hall, 1961)
This edition comprehends the main fabrication processes of metals and plastics, with special emphasis respect the economic relations that must prevail to select the chemical processes Abundant and valuable information and a treasured bibliography at the end of every chapter.